2016
DOI: 10.7862/rb.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

Badanie Zjawiska Relaksacji Naprężeń Zachodzącego W Asfaltach Drogowych Poddanych Rozciąganiu W Niskiej Temperaturze

Abstract: 1 Mieczysław SŁOWIK 2 Marta MIELCZAREK 3 BADANIE ZJAWISKA RELAKSACJI NAPRĘŻEŃ ZACHODZĄCEGO W ASFALTACH DROGOWYCH PODDANYCH ROZCIĄGANIU W NISKIEJ TEMPERATURZEW artykule przedstawiono rezultaty badań oraz analizę metody badawczej opracowanej przez autorów pracy do obserwacji zjawiska relaksacji naprężeń w lepiszczach asfaltowych w niskiej temperaturze. W badaniach wykorzystano asfalty drogowe 20/30, 35/50 i 50/70. Obserwacji zjawiska relaksacji naprężeń dokonano w warunkach stałego odkształcenia próbki spowodowa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Brass forms that were used guaranteed that cross-sectional area of every tested sample was 10 −4 m 2 . Due to the small deformation of the samples, the assumption concerning the invariant cross-section was adopted [36,37]. Analysis of the relaxation curves of asphalt binders tested at −16 • C has shown that tensile stress values are declining rapidly immediately after the force of 50 N is reached (tensile stress value decreases by a half before the first three minutes pass from the beginning of recording the force needed to retain the sample's constant elongation).…”
Section: Relaxation Test Resultsmentioning
confidence: 99%
“…Brass forms that were used guaranteed that cross-sectional area of every tested sample was 10 −4 m 2 . Due to the small deformation of the samples, the assumption concerning the invariant cross-section was adopted [36,37]. Analysis of the relaxation curves of asphalt binders tested at −16 • C has shown that tensile stress values are declining rapidly immediately after the force of 50 N is reached (tensile stress value decreases by a half before the first three minutes pass from the beginning of recording the force needed to retain the sample's constant elongation).…”
Section: Relaxation Test Resultsmentioning
confidence: 99%